2006
DOI: 10.4000/chinaperspectives.607
|View full text |Cite
|
Sign up to set email alerts
|

The Modification of the Chinese Exchange Rate Policy

Abstract: On 21st July 2005, the Chinese Central Bank revalued the yuan from 8.27 to 8.11 per US dollar. This small revaluation (2.1%) was accompanied by an official modification of the exchange rate system. The authorities announced that "the yuan will be no longer pegged to the US dollar" and that "China will reform the exchange rate regime by moving into a managed floating exchange rate regime based on market supply and demand with reference to a basket of currencies" 2. They did not publish details of the compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…In a series of studies, Cline and Williamson (2010b, a and 2011a, b) found a 40.2 percent undervaluation in January 2010, a 24.2 percent undervaluation in June 2010, a 28.5 percent undervaluation in May 2011, and a 23.5 percent undervaluation in November 2011. Goujon and Guérineau (2006) observed that 10‐15 percent misalignment is more reasonable. Even though the methods and range of Yuan undervaluation varies in these studies, it is generally agreed that the Yuan is indeed undervalued.…”
Section: Degree Of Yuan Undervaluationmentioning
confidence: 96%
See 3 more Smart Citations
“…In a series of studies, Cline and Williamson (2010b, a and 2011a, b) found a 40.2 percent undervaluation in January 2010, a 24.2 percent undervaluation in June 2010, a 28.5 percent undervaluation in May 2011, and a 23.5 percent undervaluation in November 2011. Goujon and Guérineau (2006) observed that 10‐15 percent misalignment is more reasonable. Even though the methods and range of Yuan undervaluation varies in these studies, it is generally agreed that the Yuan is indeed undervalued.…”
Section: Degree Of Yuan Undervaluationmentioning
confidence: 96%
“…Between 1995 and 2005, the Yuan was pegged to the US dollar at 8.28 Y/$ (Poleg, 2005). The USA considered the Yuan to be undervalued at this fixed rate (Goujon and Guérineau, 2006), which allowed China to export more to and import less from the USA, creating a bilateral trade deficit that has been a major concern for the USA (Labonte and Morrison, 2011). Therefore, several bills were considered by USA.…”
Section: Recent History Of Yuan Valuementioning
confidence: 99%
See 2 more Smart Citations
“…The Yuan started to appreciate from 8.11 Y/$ in 2005 to 6.83 Y/$ in 2008, and then stalled in 2008 due to the financial crisis when it was repegged to the U.S. dollar (U.S. International Trade Commission, ). It then resumed appreciation in 2010 and reached 6.21 Y/$ in 2012 (U.S. Department of Agriculture, ), but many studies conclude that the Yuan is still undervalued (Reisen, ; Goujon and Guérineau, ; Rodrik, ; Subramanian, ; Cline and Williamson, , , and ; IMF, ; U.S. Department of Treasury, ). For example, Subramanian () estimated a 30% undervaluation of the Yuan in April 2010 and Ferguson and Schularick () estimated that the Yuan was undervalued between 30% and 40% for the period of 1980–2008.…”
Section: Introductionmentioning
confidence: 99%